2021
DOI: 10.1101/2021.02.02.429485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myelin biogenesis is associated with pathological ultrastructure that is resolved by microglia during development

Abstract: To enable rapid propagation of action potentials, axons are ensheathed by myelin, a multilayered insulating membrane formed by oligodendrocytes. Most of the myelin is generated early in development, in a process thought to be error-free, resulting in the generation of long-lasting stable membrane structures. Here, we explored structural and dynamic changes in CNS myelin during development by combining ultrastructural analysis of mouse optic nerves by serial block face scanning electron microscopy and confocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 58 publications
(72 reference statements)
2
20
0
Order By: Relevance
“…However, further studies will be required to resolve the precise role of CD59 for myelin sheaths in the healthy and diseased nervous system. Interestingly, recent studies using both zebrafish and mice have revealed that individual myelin sheaths can be pruned by microglia, which may represent a form of myelin plasticity (Hughes and Appel, 2020;Djannatian et al, 2021). It is tempting to speculate that individual myelin sheaths may be susceptible to elimination if displaying a comparatively low abundance of CD59 or, vice versa, may be prevented from pruning by accumulating a high level of CD59.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies will be required to resolve the precise role of CD59 for myelin sheaths in the healthy and diseased nervous system. Interestingly, recent studies using both zebrafish and mice have revealed that individual myelin sheaths can be pruned by microglia, which may represent a form of myelin plasticity (Hughes and Appel, 2020;Djannatian et al, 2021). It is tempting to speculate that individual myelin sheaths may be susceptible to elimination if displaying a comparatively low abundance of CD59 or, vice versa, may be prevented from pruning by accumulating a high level of CD59.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have documented a number of ultrastructural myelin abnormalities, such as outfoldings, bulging, fragmentation, and splitting, that arise during early myelination but are rapidly resolved as development progresses. This research indicates that microglia are critical in removing abnormal myelination ( 40 ).…”
Section: Emergence Of Glial Populations In the Developing White Mattermentioning
confidence: 95%
“…Furthermore, these studies found that myelin sheaths that were phagocytosed were longer than sheaths that were removed through endogenous retraction, leading the authors to hypothesize that phagocytic pruning functions extend the window for myelin refinement by allowing removal of segments that have already begun to bind to the axon ( 50 ). Microglia that populate developing white matter tracts of mice have also been observed with myelin MBP inclusions ( 40 ). Abnormalities in the ultrastructure of myelin membrane have been found in the optic nerve of healthy P10 mice, but these aberrations are resolved by adulthood, indicating that occasional myelin structural errors are likely a normal part of development ( 40 ).…”
Section: Phagocytosis Of Myelin Membranementioning
confidence: 99%
“…Other recent work has utilized electron microscopy and live imaging to investigate the interactions of microglia with single oligodendrocytes and sheaths. Djannatian and colleagues used electron microscopy of the P14 optic nerve to provide evidence that microglia phagocytose abnormal myelin during development in mice and there is accumulating evidence that microglia survey myelin sheaths and phagocytose myelin in the zebrafish spinal cord during development ( Hughes and Appel, 2020 ; Djannatian et al, 2021 ). Taken together, these data show that microglia interact with myelin sheaths during development and help to ensure proper myelination.…”
Section: Extrinsic Mechanisms Regulating Premyelinating Oligodendrocyte Survival and Integrationmentioning
confidence: 99%